Lab‐on‐a‐Contact Lens: Recent Advances and Future Opportunities in Diagnostics and Therapeutics. Issue 24 (11th April 2022) - Zhu, Yangzhi; Li, Shaopei; Li, Jinghang; Falcone, Natashya; Cui, Qingyu; Shah, Shilp; Hartel, Martin C.; Yu, Ning; Young, Patric; de Barros, Natan Roberto; Wu, Zhuohong; Haghniaz, Reihaneh; et al.
Abstract: The eye is one of the most complex organs in the human body, containing rich and critical physiological information (e.g., intraocular pressure, corneal temperature, and pH) as well as a library of metabolite biomarkers (e.g., glucose, proteins, and specific ions). Smart contact lenses (SCLs) can serve as a wearable intelligent ocular prosthetic device capable of noninvasive and continuous monitoring of various essential physical/biochemical parameters and drug loading/delivery for the treatment of ocular diseases. Advances in SCL technologies and the growing public interest in personalized health are accelerating SCL research more than ever before. Here, the current status and potential of SCL development through a comprehensive review from fabrication to applications to commercialization are discussed. First, the material, fabrication, and platform designs of the SCLs for the diagnostic and therapeutic applications are discussed. Then, the latest advances in diagnostic and therapeutic SCLs for clinical translation are reviewed. Later, the established techniques for wearable power transfer and wireless data transmission applied to current SCL devices are summarized. An outlook, future opportunities, and challenges for developing next‐generation SCL devices are also provided. With the rise in interest of SCL development, this comprehensive and essential review can serve as a new paradigm for the SCL devices. Abstract : Smart Contact lens (SCL) platforms have emerged as a promising interface between the eye and electronic devices for personalized healthcare applications. This review summarizes the state‐of‐the‐art in material synthesis, device manufacturing, and system integrations of SCLs and provides recent progress and future opportunities of SCL as an effective diagnostic and therapeutic tool.